Effect of Aerobic Exercise on Lipid Metabolism in Rats With NAFLD - Zhou, Tongxi; Niu, Mengfan; Liu, Ruichen; Li, Li (Frontiers in Genetics, 2022)
This work aimed to study the intervention effect of exercise on lipid metabolism in NAFLD rats, provide a more scientific experimental basis for exploring and improving the theoretical system of exercise intervention in NAFLD, and further provide a theoretical research basis for clinical treatment of NAFLD. Forty healthy male Sprague Dawley rats were randomly divided into a blank control group (BC,14) and a model group (MO, 26). After 6°weeks of modeling, the MO group was randomly divided into the model control group (MC, 12) and the aerobic exercise group (AE, 12). Platform running intervention in group E was conducted at a slope of 0°, a speed of 15 m/min, 1 h/time, once a day, six times a week, and a day of rest, for 8°weeks in total. After the intervention, the liver tissues of rats were taken for pathological sections, and serum was taken and analyzed for TC, TG, LDL-C, HDL-C, and FFA levels. Under the light microscope, the liver tissue structure of rats in the BC group was complete and clear, the structure of liver lobules was clear and normal, the volume of hepatocytes was uniform, the nucleus was in the middle, and the cytoplasm was red-stained, and no steatosis of hepatocytes was found. The liver of rats in the MC group showed diffuse fatty lesions, disordered structure of hepatic lobules, disordered arrangement of hepatic cords, different sizes of hepatocytes, loose cytoplasm, and diffuse lipid droplets of different sizes in the cytoplasm. The accumulation of liver lipid droplets in the AE group was improved compared with the MC group, the number of fat vacuoles in hepatocytes was significantly reduced, and the degree of liver lipid deposition was reduced. Compared with the BC group, the content of TC, TG, LDL-C, and FFA in the serum of the MC group increased significantly (p < 0.01), and the content of HDL-C decreased significantly (p < 0.01). Compared with the MC group, the content of TC, TG, LDL-C, and FFA in the serum of the AE group decreased significantly (p < 0.01/p < 0.05), and the content of HDL-C increased significantly (p < 0.01). Therefore, moderate-intensity aerobic exercise has an intervention effect on lipid metabolism in NAFLD rats, which can be used as one of the means to treat NAFLD.